Physical chemistry of functionalised biomedical nanoparticles : University of Bristol, UK, 17-19 September 2014 - Eagling, Robert; Royal Society of Chemistry (Great Britain). Faraday Division (Cambridge : Royal Society of Chemistry, 2014)
'This Faraday Discussion focuses on one very fundamental issue of nanoparticle (NP) research: functionalisation specifically related to biomedical applications. Without the right functionalisation, NPs will be rendered useless, therefore how can NPs be synthesised with the desired functionality? Nanotechnology, especially nanoparticle research, has played a very important role in many scientific discoveries, laying the foundation for its application in many aspects of our lives, such as healthcare, efficient energy and cleaner environments. The field is moving very quickly, with an ever-increasing number of researchers. This volume will promote deep discussion on a topic that has previously been neglected. The whole field would stand still without the availability of appropriate functionalisations for specific applications. The latest research and discussion presented here on this very important issue will help to harness the full potential of nanoparticle research.'--Back cover.
'A general discussion on the Physical Chemistry of Functionalised Biomedical Nanoparticles was held in Bristol, UK on the 17th, 18th and 19th of September 2014.'
Includes bibliographical references.
Keywords: Nanoparticles -- Congresses; Biomedical materials -- Congresses; Nanostructured materials -- Congresses